Mesenchymal Stem/Stromal Cells Derived from Dental Tissues: A Comparative In Vitro Evaluation of Their Immunoregulatory Properties Against T cells - María del Pilar De la Rosa-Ruiz; Marco Antonio Álvarez-Pérez; Víctor Adrián Cortés-Morales; Alberto Monroy-García; Héctor Mayani; Gladis Fragoso-González; Sara Caballero-Chacón; Daniel Diaz; Fernando Candanedo-González; Juan José Montesinos (Cells, 2019)
Bone marrow mesenchymal stem/stromal cells (BM-MSCs) have immunoregulatory properties and have been used as immune regulators for the treatment of graft-versus-host disease (GVHD). Human dental tissue mesenchymal stem cells (DT-MSCs) constitute an attractive alternative to BM-MSCs for potential clinical applications because of their accessibility and easy preparation. The aim of this in vitro study was to compare MSCs from dental pulp (DP-MSCs), gingival tissue (G-MSCs), and periodontal ligament (PDL-MSCs) in terms of their immunosuppressive properties against lymphoid cell populations enriched for CD3+ T cells to determine which MSCs would be the most appropriate for in vivo immunoregulatory applications. BM-MSCs were included as the gold standard. Our results demonstrated, in vitro, that MSCs from DP, G, and PDL showed immunoregulatory properties similar to those from BM, in terms of the cellular proliferation inhibition of both CD4+- and CD8+-activated T-cells. This reduced proliferation in cell co-cultures correlated with the production of interferon-γ and tumor necrosis factor alpha (TNF-α) and the upregulation of programmed death ligand 1 (PD-L1) in MSCs and cytotoxic T-cell-associated Ag-4 (CTLA-4) in T-cells and increased interleukin-10 and prostaglandin E2 production. Interestingly, we observed differences in the production of cytokines and surface and secreted molecules that may participate in T-cell immunosuppression in co-cultures in the presence of DT-MSCs compared with BM-MSCs. Importantly, MSCs from four sources favored the generation of T-cell subsets displaying the regulatory phenotypes CD4+CD25+Foxp3+ and CD4+CD25+CTLA-4+. Our results in vitro indicate that, in addition to BM-MSCs, MSCs from all of the dental sources analyzed in this study might be candidates for future therapeutic applications.